A Cross-Sectional Survey on Dietary Supplements Consumption among Italian Teen-Agers - del Balzo, Valeria (Public Library of Science, 2014)
INTRODUCTION: In the last decades, dietary supplements consumption has increased in the Western world for all age groups. The long-term potentially dangerous effects related to an indiscriminate consumption of dietary supplements are still unknown and are becoming a matter of public health concern. Therefore, the aims of the present study were: to explore the contribution of dietary supplements to micronutrient daily intake, and to evaluate awareness and knowledge about dietary supplements. METHODS: Participants (age ranging from 14 to 18 years) were recruited among students attending 8 high schools in the province of Frosinone (Italy). An anonymous questionnaire, composed of 12 multiple-choice items, was administered to all the participants. T-test and the analysis of variance (ANOVA) were performed to describe differences between means of the groups, while the chi-square test was used to compare observed and expected frequencies. The logistic regression model, aimed at identifying the characteristics of potential consumers of dietary supplements, RESULTS: A total of 686 teenagers (288 males and 398 females, average age: 17,89±0,91 years) participated in the study. The 83,6% of participants affirmed to be aware of dietary supplements. 239 participants consumed dietary supplements: 118 males and 121 females. 49,1% of females consumed dietary supplements less than twice a week, whereas 43,6% of males consumed dietary supplements from 2 to 5 times per week. Statistically significant differences emerged between the genders with respect to the source of information regarding dietary supplements, the perceived indications for their use, and the choice of the store/place to purchase them. DISCUSSION: Findings in the present study provide insight into the consumption of dietary supplements among young Italians, highlighting the need to foster further awareness among adolescents about the correct use of dietary supplements, especially in terms of indications and contraindications.